Do family planning programmes help women's employment? The case of Indian mothers - Gianna Claudia Giannelli; Francesca Francavilla (Institute for the Study of Labor (IZA), 2007)
The paper deals with female employment in developing countries. We set out a model to test our argument that, at the first stage of development, demographic and health programmes have proven to be more effective for women's position in the society than specific labour and income support policies. Our household model in the collective framework predicts that an exogenous improvement in household production technology due to demographic and health policies gives the wife the opportunity to employ her time resources more efficiently, and, by consequence, the power to choose to participate or not to the labour market. A unique, rich and representative data survey for all Indian states and rural India (NFHS-2, 1998-1999) allows us to analyse the role of Family Planning (FP), reproductive and child care programmes, for the employment probability of married women aged 15 to 49. Our results for urban and rural India show that the FP effect is significant in rural India, that is, women that have been visited by an FP public worker have a higher probability of being employed. Moreover, for rural India, we compare this effect with that one of Governmental Policies (GP) supporting household income and promoting employment. Our results show that the effect of this particular FP intervention has been more effective for women's employment than GP. This result appears to be robust across different definitions of female employment and model specifications.
urn:nbn:de:101:1-20080402129
Keywords: 330; Frauenerwerbstätigkeit; Mütter; Familienplanung; Kinderbetreuung; Indien; Entwicklungsländer